Dynamic Torque Limitation vs Static Torque Limitation for Bone Screws in Pig Bone - Wilkie Jack; Richard Jordan; Joshi Aditya; McFarlane Zoe; Staiger Mark; Rauter Georg; Möller Knut (Current Directions in Biomedical Engineering)
Correctly torquing bone screws is important to achieve good patient outcomes. An automated system has been previously proposed that may allow more objective torquing of bone screws. Here the system is tested vs. a static torque limit in pig bone. 5 screws were first inserted until stripping to calibrate the dynamic and static limits. Then 6 were inserted limited to 80% of the mean stripping torque. Then 7 were inserted using 80% of the dynamic model-predicted stripping torque. The pull-out strength of the dynamic and static insertions were compared and no statistically significant difference was found. Future work should consider at using larger screws and different bone samples, with more repetitions to try and obtain a statistically significant result.